BILATERAL RELATIONSHIP BETWEEN TOURISM AND CLIMATE CHANGE: IMPACTS, VULNERABILITY & SOLUTIONS (International Association of Biologicals and Computational Digest, 2022)
Human activities are directly or indirectly assigned to “Climate change”. Global scenario indicates that changing climate is an influencing phenomenon with wide range of impacts on different levels in societies and industries. In current scenario tourism industry is considered as one of the fastest-growing industries with direct relation to changing climate. Tourism is totally dependent on various climatic conditions over specific destinations. Any effort to separate them will lead to danger. Tourism is one of the fastest-growing industries which is also responsible for excess amount of emissions and also includes large scope to adapt or mitigate changing climate. Tourism has the capability to create beneficial effects on the environment by contributing to environmental protection and conservation. It is a way to raise awareness of environmental values and it can serve as a tool for foreign investments. As tourism is a growing sector it is essential to identify its promising impacts on climate change. With marked increase in tourism industry it is quite easy to understand the flow of tourist by statistical analysis of secondary data, and its relative possible impacts. Lack of research in sustainable tourism and climate change provides us platform to built bilateral approach for solutions using micro observations of destination as well as generation of primary data using socio-economic methods. This approach for sustainable tourism and its advantages play a major role in global context. Tourism, a highly growing industry is also providing various possibilities to achieve sustainable development goals (SDGs) and to stabilize the global threat of 21st century.
Keywords: Global scenario, Bilateral approach, Sustainable tourism, SDGs.